Mapping the Level of Earthquake Hazards in Banyuwangi Region Based on Peak Ground Acceleration - Ghofur, Muhamad Abdul; Sukarasa, I Ketut; Darsono, Rudy (BULETIN FISIKA; Vol 23 No 1 (2022): BULETIN FISIKA February EditionDO - 10.24843/BF.2022.v23.i01.p06, 2021)
Banyuwangi area is an earthquake prone area because it is close to the megathrust zone (indo-Australian and Eurasian plate junction) and back arc. The aim of this research is to determine the most suitable empirical formula for Banyuwangi area and to determine the level of earthquake hazard in Banyuwangi region. The peak ground acceleration value is determined by comparing 5 empirical equations, namely the empirical formula of Mc. Guirre R.K (1963), Esteva (1970), Donovan (1973), Setiawan (2012), and Fukushima & Tanaka (1990). The results show that the empirical formula Setiawan is the most suitable formula among other empirical formula.  The largest earthquake hazard level is in the eastern Banyuwangi region in the scale of VII-VIII MMI, with the highest peak ground acceleration value of 301,801 gal.